Macrophage-Osteoclast Associations: Origin, Polarization, and Subgroups - Sun, Yang; Li, Jiangbi; Xie, Xiaoping; Gu, Feng; Sui, Zhenjiang; Zhang, Ke; Yu, Tiecheng (Frontiers in Immunology, 2021)
Cellular associations in the bone microenvironment are involved in modulating the balance between bone remodeling and resorption, which is necessary for maintaining a normal bone morphology. Macrophages and osteoclasts are both vital components of the bone marrow. Macrophages can interact with osteoclasts and regulate bone metabolism by secreting a variety of cytokines, which make a significant contribution to the associations. Although, recent studies have fully explored either macrophages or osteoclasts, indicating the significance of these two types of cells. However, it is of high importance to report the latest discoveries on the relationships between these two myeloid-derived cells in the field of osteoimmunology. Therefore, this paper reviews this topic from three novel aspects of the origin, polarization, and subgroups based on the previous work, to provide a reference for future research and treatment of bone-related diseases.